2011
DOI: 10.1097/qad.0b013e3283437ed7
|View full text |Cite
|
Sign up to set email alerts
|

Association of aging and survival in a large HIV-infected cohort on antiretroviral therapy

Abstract: As antiretroviral treatment cohorts mature, the proportion of patients who are elderly will inevitably increase. Elderly patients may require focused clinical care that extends beyond HIV treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 26 publications
9
33
1
1
Order By: Relevance
“…For instance, the proportion of males compared to females was higher among the older adults. This has been noted previously 19,20,22 and the explanation this is probably a result of older men having younger women as intimate partners. Partially, this could be supported by the higher proportion of females (almost two-thirds) among younger patients.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…For instance, the proportion of males compared to females was higher among the older adults. This has been noted previously 19,20,22 and the explanation this is probably a result of older men having younger women as intimate partners. Partially, this could be supported by the higher proportion of females (almost two-thirds) among younger patients.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, there are some studies from SSA 19-23 . These studies have reported on various aspects, mainly mortality 19,20,22 , with some reporting on immunological response 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Home-based counseling and testing (HBCT) is a potential strategy for early identification of patients prior to the severe depletion of their CD4 T cells. This strategy is necessary to link up at-risk populations such as adolescents, men, and the elderly who usually have poor health seeking behaviors with treatment programs, [44,45] thereby ensuring better health outcomes. It is also important for early identification of discordant couples and linking them up with treatment, care, and support to prevent further viral spread.…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, kematian lebih cepat terjadi dalam empat tahun pertama semenjak terapi antiretroviral dimulai. 3 Belum diketahui pasti penyebabnya, namun diperkirakan perhatian yang kurang terhadap kepatuhan berobat, interaksi obat dan toksisitas, serta komorbid multipel memiliki pengaruh. Dengan demikian, dibutuhkan pendekatan tersendiri dalam menangani pasien HIVusia lanjut.…”
Section: Pendahuluanunclassified